2019
DOI: 10.3389/fnhum.2019.00139
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Plasticity in Reading-Related Pathways Differs in Children Born Preterm and at Term: A Longitudinal Analysis

Abstract: Children born preterm (PT) are at risk for white matter injuries based on complications of prematurity. They learn to read but on average perform below peers born full term (FT). Studies have yet to establish whether properties of white matter pathways at the onset of learning to read are associated with individual variation later in reading development in PT children. Here, we asked whether fractional anisotropy (FA) at age 6 years is associated with reading outcome at age 8 years in PT children in the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 87 publications
5
49
1
Order By: Relevance
“…1 . Specifically, we identified tracts of a dorsal pathway, the Arc-L ( Dodson et al, 2018 , Travis et al, 2016 ) and two bilateral ventral pathways, the ILF-L and ILF-R, and the UF-L and UF-R ( Beaulieu et al, 2005 , Ben-Shachar et al, 2007 , Bruckert et al, 2019a , Dodson et al, 2018 , Travis et al, 2016 , Travis et al, 2017 , Vandermosten et al, 2012 ). Additionally, we examined the CC-Occ to capture posterior white matter regions associated with language related skills ( Dougherty et al, 2007 , Dubner et al, 2019 , Frye et al, 2008 , Hasan et al, 2012 , Huber et al, 2019 , Odegard et al, 2009 ) and susceptible to injuries from PT-birth related complications ( Back, 2015 , Volpe, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 . Specifically, we identified tracts of a dorsal pathway, the Arc-L ( Dodson et al, 2018 , Travis et al, 2016 ) and two bilateral ventral pathways, the ILF-L and ILF-R, and the UF-L and UF-R ( Beaulieu et al, 2005 , Ben-Shachar et al, 2007 , Bruckert et al, 2019a , Dodson et al, 2018 , Travis et al, 2016 , Travis et al, 2017 , Vandermosten et al, 2012 ). Additionally, we examined the CC-Occ to capture posterior white matter regions associated with language related skills ( Dougherty et al, 2007 , Dubner et al, 2019 , Frye et al, 2008 , Hasan et al, 2012 , Huber et al, 2019 , Odegard et al, 2009 ) and susceptible to injuries from PT-birth related complications ( Back, 2015 , Volpe, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study was designed to determine (1) if language outcomes at 2 years related to variability in white matter microstructure in language-related white matter tracts on pre-discharge dMRI scans in PT infants, beyond the influence of developmental age at scan and neonatal medical complications and (2) whether the number of medical complications moderated any effects. We obtained measures for FA and MD from specific white matter pathways commonly implicated in processing linguistic information ( Hickok and Poeppel, 2007 ) and in tracts in which white matter metrics and language related measures have been associated in PT children, including a dorsal pathway, the Arc-L ( Dodson et al, 2018 , Travis et al, 2016 ) and two bilateral ventral pathways, the ILF-L and ILF-R, and the UF-L and UF-R ( Beaulieu et al, 2005 , Ben-Shachar et al, 2007 , Bruckert et al, 2019a , Dodson et al, 2018 , Travis et al, 2016 , Travis et al, 2017 , Vandermosten et al, 2012 ). Additionally, we examined fiber pathways traversing the occipital segment of the corpus callosum (CC-Occ) for three reasons: (1) Intrahemispheric connections are postulated to play an important role in language processing in infancy ( Perani et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…FT children's reading skills are associated with white matter microstructural metrics derived from dMRI (10,11). Associations in dorsal pathways, including the arcuate fasciculus (Arc) and superior longitudinal fasciculus (SLF) (7,(10)(11)(12), are thought to relate to transmission of phonological information for converting visual word forms to spoken words (13). Associations in ventral pathways, including the inferior longitudinal fasciculus (ILF) and the uncinate fasciculus (UF) are thought to relate to transmission of semantic and orthographic information (7,12,14,15).…”
Section: Short Title: Reading and Cortical White Matter In Preterm Chmentioning
confidence: 99%
“…Associations in dorsal pathways, including the arcuate fasciculus (Arc) and superior longitudinal fasciculus (SLF) (7,(10)(11)(12), are thought to relate to transmission of phonological information for converting visual word forms to spoken words (13). Associations in ventral pathways, including the inferior longitudinal fasciculus (ILF) and the uncinate fasciculus (UF) are thought to relate to transmission of semantic and orthographic information (7,12,14,15). Individual differences in reading among PT children have also been associated with white matter microstructural metrics (16)(17)(18).…”
Section: Short Title: Reading and Cortical White Matter In Preterm Chmentioning
confidence: 99%
“…Regional white matter DTI has been correlated to language ability and pre-reading skills in younger ''pre-readers'' (Saygin et al, 2013;Vandermosten et al, 2015;Wang et al, 2017;Dodson et al, 2018;Vanderauwera et al, 2018;Walton et al, 2018;Ozernov-Palchik et al, 2019;Hutton et al, 2020), and even in infants with a family history of developmental dyslexia (Langer et al, 2017). Longitudinal DTI has shown that both baseline values and changes of diffusion parameters between scans predict future reading ability in healthy controls (Hoeft et al, 2011;Yeatman et al, 2012;Myers et al, 2014;Gullick and Booth, 2015;Takeuchi et al, 2016;Vanderauwera et al, 2017;Borchers et al, 2019;Bruckert et al, 2019;Lebel et al, 2019) and in neurodevelopmental disorders such as fetal alcohol spectrum disorders (Treit et al, 2013). Further compelling evidence of a link between regional white matter plasticity and function comes from DTI parameter changes with remediation in grade-school poor readers (Keller and Just, 2009;Huber et al, 2018), training in spelling-impaired children (Gebauer et al, 2012), and acquisition of literacy in those learning to read in adulthood (Thiebaut de Schotten et al, 2014).…”
Section: Introductionmentioning
confidence: 99%